Spatial Construction of the Finnish Region in Finnish-Language Fiction 1870–1944 - Nivala, Asko; Saarelainen, Juhana; Westerlund, Jasmine (AVAIN - Kirjallisuudentutkimuksen aikakauslehti, 2024)
In this article, we examine the spatial construction of the Finnish region in Finnish-language literature. We apply methods of literary cartography, language technology and geographic information systems. Our data consists of 840 digitised Finnish-language volumes from the period 1870–1944. Using language technology, we recognise place names from the material and use the spatial database created from this as the starting point for our research process. With the database, we have uncovered many lesser-studied works in which the definition of Finland’s territory is a central theme. We conduct close readings of these works, focussing on the geographical space they construct. In our analysis of narrative space, we utilise Mikhail Bakhtin’s concept of the chronotope. Additionally, we use maps based on the results of named entity recognition. We structure our article regionally, focusing on Western Finland, Karelia and Lapland. In each region studied, we show how literature from the late nineteenth and early twentieth centuries sought to construct an image of a territorially unified Finland. Especially Karelia and Lapland were depicted not only as idealised natural spaces but also as problematic areas whose inclusion in Finland had to be specifically justified, as these regions were also home to Karelian and Sámi populations. Our material highlights that the historical novel is a particularly place-dense and spatially oriented genre. Tutkimme artikkelissamme Suomen alueen maantieteellistä rajaamista suomenkielisessä kaunokirjallisuudessa. Sovellamme artikkelissamme kirjallisen kartografian menetelmiä, kieliteknologiaa ja paikkatietojärjestelmiä. Aineistona on 840 digitoitua suomenkielistä nidettä aikaväliltä 1870–1944. Olemme tunnistaneet aineistosta kieliteknologian avulla paikannimiä. Käytämme tästä syntynyttä paikkatietokantaa tutkimusprosessin lähtökohtana. Tietokannan avulla olemme löytäneet monia vähemmän tutkittuja teoksia, joissa Suomen alueen määrittely on keskeisenä teemana. Tämän jälkeen lähiluemme ...